An International Comparison of Equity in Accessibility to Jobs: London, São Paulo and the Randstad - John P. Pritchard; Diego Tomasiello; Mariana Giannotti; Karst Geurs (Findings)
We analyze the impact of different accessibility measures on the interpretation of associated equity analysis using the Gini Coefficient and the (pseudo) Palma Ratio, and the impact of the method of assigning zonal accessibility on Gini estimation results using four different alternatives. Two types of potential accessibility measures (zonal and person-based) and two ratios of potential jobs to potential population (intra-modal and multi-modal) are estimated for car and transit in the Netherlands’ Randstad region, Greater London, and São Paulo relying on network data, schedule-based data, and speed profiles. Gini results are heavily influenced by the accessibility indicator and the method of assignment. The Palma ratio is also influenced by the choice of accessibility indicator, with the person-based potential accessibility measure tending to show greater inequity.